Primary care and healthcare utilization among older Brazilians (ELSI-Brazil) - James Macinko; Fabíola Bof de Andrade; Paulo Roberto Borges de Souza Junior; Maria Fernanda Lima-Costa (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE To characterize healthcare access and utilization among older Brazilians. METHODS Data are from the baseline wave of the Brazilian Longitudinal Study of Aging (ELSI-Brazil), which is a nationally representative, population-based cohort study of persons aged 50 years and older conducted in 2015/2016 (n = 9,412). The prevalence of barriers to primary care and number and type of doctor visits in the past 12 months are compared by three main sources of healthcare (private, Family Health Strategy, traditional public clinics). Two-part multivariable hurdle analyses assess the relation between healthcare utilization, primary care problems, and source of healthcare, while controlling for healthcare determinants. RESULTS Females comprised 54% of the sample, with a mean age of 63 years. There were no demographic differences by source of healthcare. Nearly 83% had at least one doctor visit in the past 12 months, with higher use among private health plan holders. Private health plan holders most frequently visited specialists, while those using the public system were more likely to visit a general practitioner. Primary care barriers averaged 3.5 out of 12 and were the highest among those using traditional health posts. A greater number of primary care problems was negatively associated with all types of healthcare utilization. CONCLUSIONS By international standards, access to basic healthcare among older Brazilians is relatively high. Nevertheless, different levels of primary care problems between the public and private sectors and resulting utilization patterns suggest the need to continue working to close remaining gaps.